2023
DOI: 10.3389/fcell.2023.1119220
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein candidates in spermatozoa of water buffalo (Bubalus bubalis) bulls helps in predicting their fertility status

Abstract: The water buffalo (Bubalus bubalis) is an indispensable part of the Indian dairy sector and in several instances, the farmers incur economic losses due to failed pregnancy after artificial insemination (AI). One of the key factors for the failure of conception is the use of semen from the bulls of low fertilizing potential and hence, it becomes important to predict the fertility status before performing AI. In this study, the global proteomic profile of high fertile (HF) and low fertile (LF) buffalo bull sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…In our study, the Western blot analysis observed significantly decreased SP17 expression, and this was in coherence with the 2-DE results ( Figure 3 F and Figure 4 E). Previously, SP17 has been shown to be abundantly expressed in high-fertile buffalo bulls (conception rates: 51% to 56.7%) compared with that in low-fertile bulls (conception rates: 28.8% to 33.8%; log 2-fold change = 2.47) [ 42 ]. Consistent with previous research, the findings of the current study showed that low SP17 expression is correlated with decreased fertility parameters, including sperm motility and intracellular ATP levels ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the Western blot analysis observed significantly decreased SP17 expression, and this was in coherence with the 2-DE results ( Figure 3 F and Figure 4 E). Previously, SP17 has been shown to be abundantly expressed in high-fertile buffalo bulls (conception rates: 51% to 56.7%) compared with that in low-fertile bulls (conception rates: 28.8% to 33.8%; log 2-fold change = 2.47) [ 42 ]. Consistent with previous research, the findings of the current study showed that low SP17 expression is correlated with decreased fertility parameters, including sperm motility and intracellular ATP levels ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, details concerning their presence in seminal plasma, their significance in sperm metabolism, and their relation to bull fertility were not investigated extensively [8, 9,10]. The proteins in seminal plasma have an essential role in sperm protection, their capacitation inside the female reproductive tract, acrosome reaction, sperm-egg binding, and early conception and embryonic development [11,12]. Detection of seminal proteins for good and bad semen will provide further details concerning the early prediction of buffalo bull fertility via their role in sperm metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the semen of buffaloes is more susceptible to lipid oxidative damage by reactive oxygen species (ROS), which leads to an increase in the percentage of abnormalities, damage to the genetic material, and a decrease in fertility [9,10]. Buffalo bulls are characterized by a lack of sperm concentration, motility, viability, a weak sperm mitochondrial membrane, and maturation within the epididymis [11]. The effects of reactive oxygen species on the semen of buffalo bulls appear during spermatogenesis and cryopreservation [6,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In semen, free radicles or ROS are generated by leukocytes, dead, abnormal, and immature spermatozoa. Buffalo bulls are characterized by a lack of sperm concentration, motility, and viability, a weak sperm mitochondrial membrane, and maturation within the epididymis [12]. The effects of free radicals or ROS on the semen of buffalo bulls appear during spermatogenesis and cryopreservation [6,11,13,14].…”
Section: Introductionmentioning
confidence: 99%